Youthnation : - Britton, Matthew (John Wiley and Sons, 2015)
YouthNation is an indispensable brand roadmap to the youth-driven economy. Exploring the idea that youth is no longer an age—it's a commodity that's available to everyone—this book shows what it takes to stay connected, agile, authentic, and relevant in today's marketplace. Readers will learn the ins and outs of the new consumer, and the tools, methods, and techniques that ensure brand survival in the age of perpetual youth. Coverage includes marketing in a post-demographic world, crafting the story of the brand, building engaged communities, creating experiences that inspire loyalty and evangelism, and the cutting-edge tricks that help businesses large and small harness the enormous power of youth.